An Evaluation of Taxpayers’ Perception of Value Added Tax and Cost of Living in Nigeria - Oluwatobi, Johnson Adenike; Omodero, Cordelia Onyinyechi; Ololade, Babatunde Moses; Ekundayo, Gbenga; Odhigu, Festus Onosakponome (International Review of Management and Marketing, 2024)
This study evaluates taxpayers’ perception of value added tax (VAT) and cost of living in Nigeria. The main focus of this research is to evaluate the awareness and opinion of individuals, households and organizations regarding VAT, and to understand the relationship between perception and compliance with VAT regulations. Furthermore, the study examines how VAT affects cost of living and provision of social amenities funded by the revenue generated from this tax. Questionnaires were used to collect data and outcomes were analysed using mean of simple percentage and frequency count. Statistical Package for Social Sciences (SPSS 20.0) and the SEM-PLS (4) were used to evaluate the hypotheses. The analysis showed that there is significant relationship between the level of VAT awareness and provision of social amenities. The result showed that perception about VAT has a significant influence on provision of social amenities, level of VAT awareness significantly influences compliance with VAT regulations, perceptions about VAT significantly influences compliance with VAT regulations and lastly perception about VAT significantly influence cost of living. It is recommended that the government should enhance awareness about VAT and address diverse opinions on perception in order to increase compliance with VAT regulations leading to efficient provision of social amenities and an improved of cost of living. Implementing strategies that could inform more effective tax policies and compliance strategies is essential to support economic growth and development.